Hydrothermal Synthesis of MnO2 and Hemp-Derived Activated Carbon Composites for Tailored Electrochemical Performance - Klangvijit, Kanisorn; Bowornthommatadsana, Khemjiranee; Reilly, Mayuree Phonyiem; Obata, Michiko; Fujishige, Masatsugu; Takeuchi, Kenji; Wongwiriyapan, Winadda; Endo, Morinobu (My University, 2026)
This study investigates hydrothermal synthesis of manganese dioxide composited with hemp-derived activated carbon (MnO2/AC) as electrodes for supercapacitors. The effects of key hydrothermal parameters, including carbon ratio, reaction temperature, and reaction time were systematically examined. Phase-pure α-MnO2 was uniformly anchored on carbon framework. Morphology of MnO2 evolved from nanowalls to well-defined nanorods with increasing reaction temperature and time. Meanwhile, the specific surface area of MnO2/AC decreased from 1712 to 1538 m2 g−1 due to partial pore blocking, while a predominantly mesoporous structure was retained. Electrochemical measurements in 1 M Na2SO4 demonstrate that the optimized MnO2/AC composites achieve a specific capacitance of 216.8 F g−1 at 1 A g−1. Charge-storage mechanism analysis reveals a balanced contribution between surface-controlled capacitive processes and diffusion-controlled pseudocapacitance, which is directly correlated with preserved mesoporosity and moderate MnO2 coverage. When the MnO2/AC composites were assembled into an asymmetric supercapacitor using AC as the negative electrode, the device operates stably up to 2.4 V and delivers outstanding cycling stability over 95% after 22,000 charge–discharge cycles at 5 A g−1. These results demonstrate that controlled growth of MnO2, rather than maximum oxide loading, is essential for optimizing charge-storage mechanisms and achieving high-performance biomass-derived supercapacitor electrodes.
Keywords: asymmetric supercapacitor; charge-storage mechanism; hemp-derived activated carbon; hydrothermal synthesis; MnO2/activated carbon composite